"Everything Is Interrelated": The COVID‐19 Pandemic and Integral Ecology. Issue 4 (16th December 2020) - Kerber, Guillermo
Abstract: The COVID‐19 pandemic has shown that "everything is interrelated, " especially in relation to health, ecology, economy, and climate change, as various authors have stated. The motto is the leitmotif of Pope Francis' encyclical Laudato si' and leads to his proposal of an integral ecology. This article deepens the implications of the latter in the encyclical and in other works and shows how the Catholic Synod of Bishops for the Pan‐Amazon Region is an example of the reception and application of integral ecology in a given context. Based on this, the article proposes some conclusions, taking into account the theme of the next assembly of the World Council of Churches in 2022.